Tradable immigration quotas - Jesús Fernández-Huertas Moraga; Hillel Rapoport (Institute for the Study of Labor (IZA), 2011)
International migration is maybe the single most effective way to alleviate poverty at a global level. When a given host country allows more immigrants in, this creates costs and benefits for that particular country as well as a positive externality for all those (individuals and governments) who care about world poverty. This implies that the existing international migration regime is inefficient as it fails to internalize such externality. In addition, host countries quite often restrict immigration due to its apparently unbearable social and political costs. However these costs are never measured and made comparable across countries. In this paper we first discuss theoretically how tradable immigration quotas (TIQs) can reveal information on such costs and, once coupled with a matching mechanism taking into account migrants' preferences, generate substantial welfare gains for all the parties involved. We then propose two potential applications: a market for the resettlement of international (e.g., climate change) refugees, and an extension of the US diversity lottery to a larger set of host countries and other immigration targets. Both applications are seen as possible precursors to a full implementation of a TIQs system.
urn:nbn:de:101:1-20110621249
Keywords: F22; F5; H87; I3; K33; O19; 330; immigration; immigration policy; tradable quotas; refugees; climate change; international public goods